Kepemimpinan K.H Abdul Aziz Choiri dalam Meningkatkan Kualitas Pemahaman Agama dan Akhlak Pada Santri di Pondok Pesantren Al-Ma’ruf 1 Kranggan Lamongan - Aslamiyah, Siti Suwaibatul; Yukha, Imanda Ni’ma (Universitas Islam Lamongan, 2023)
This research is entitled Leadership K.H Abdul Aziz Choiri in improving the quality of understanding religion and morals in students at the Al-Ma’ruf 1 islamic boarding school Kranggan Lamongan. Al-Ma’ruf 1 islamic boarding school is the goal of the researcher because the islamic boarding school has its own characteristics, namely freeing all its students to choose formal education according to their wishes around the islmic boarding school so that apart from gaining religious knowledge they can also gain world knowledge through these formal institutions. The purpose of this study was to determine the leadership strategy and model of K.H Abdul Aziz Choiri in improving the quality of religious an moral understanding of students at the Al-Ma’ruf 1 Kranggan Lamongan. This research is a type of qualitative research an a phenomenological approach. From the results of this study. K.H Abdul Aziz Choiri has several models in his leadership, namely charismatic, adaptive, participatory, and entrepreneurial. The second is the strategy carried out by K.H Abdul Aziz Choiri in improving the quality of understanding religion and morals ini students, the strategy used by K.H Abdul Aziz Choiri is to set an example, teach, habituate, give gifts, and give threats or punishment.